ANALISIS PERANCANGAN APLIKASI SISTEM INFORMASI E-MCARD BERBASIS ANDROID PADA PT. XYZ - Sari, Meritha Indah; Djahidin, Danny Yudin (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
PT. XYZ is a local Indonesian pharmaceutical company that is currently developing,where in the development of a company the role of Information Technology is very important along with the very rapid development.PT. XYZ in the application of Information Technology data processing is quite good and has an information system that can be used to analyze data. But there are still problems in the process of making a report about a Marketing employees visit that affects the salaries and incentives of the Marketing department.The purpose of this study is to be able to measure the process of achieving the target of visits given by the Company to each of the Marketing Department Employees,product promotion to doctors, and help monitor sales targets, where researchers use the SWOT and Fishbone Analysis Methods in the analysis process. Keywords: Analisis, Perancangan, Android, SWOT, Fishbone